Discrimination Against Ahmadiyah In The Outcast Novel By Okky Madasari (2014): A Sociological Approach - Oktafiana R, Anika; , Dr. Phil. Dewi Candraningrum, M.Ed; , Titis Setyabudi, S.S. M. Hum (2015)
This research paper aims to know discrimination against Ahmadiyah of the major character reflected in The Outcast novel. The objective of the research is to analyze Okky Madasari's The Outcast novel based on the structural elements of the novel and to analyze the religious conflicts by using sociological theory. The type of this research is descriptive qualitative. The data of the research is the primary data of the research is The Outcast novel by Okky Madasari. The secondary data of the research taken from any information related to the novel such as books, other source and website that related to the study. The technique of collecting data are reading novel, taking important note from primary and secondary data, arranging the data into several part based on its classification, selecting the data by rejecting the irrelevant information which does not support the topic of the study, and drawing the conclusion. The method to analyze of this data is descriptive analysis. Based on structural elements of the novel, the writer delivers a moral message that "The discrimination can be caused by the lack of knowledge". The result of this analysis is that the discrimination against Ahmadiyah in the novel appears in a form of direct and indirect discrimination.The first discrimination appears in the middle of Ahmadi community it self, where the Ahmadi can not make relationship with outsider. Not only in her family of Ahmadi, has Alam's parent also considered their decision related with the rule of their faith.